Personality Types in relation to dental caries and salivary testosterone among teachers in Baghdad city - Al dafaai, Raya R; Diab, Ban S; Abd Al Ghani, Huda J (Journal of Baghdad College of Dentistry, 2019)
Background: Personality could be defined broadly as those characteristics of individuals that describe the pattern of feeling, cognition and behaving. Personality types can be measured by using one of personality typeâ€™s measures. Personality has been proposed to influence the oral health. The purpose of the present study was to assess the influence of Personality Types on caries experience in relation to salivary testosterone hormone among teachers in Baghdad city. Materials and Methods: Female teachers (n=534) of randomly selected schools were subjected to personality questionnaire using The Riso-Hudson Enneagram Type Indicator. Teachers were examined to estimate the caries experience according to the decayed-missing and filled index (DMFS). A group of teachers were randomly selected from the total sample for salivary analysis of testosterone. Data were analyzed using SPSS version 18 software. A probability value less than 0.05 was considered to be statistically significant. Results: Data analysis showed that the higher percentage of teachers was Helpers as the dominant Type. The results showed statistical high significant differences in mean values of DMFS among the nine Personality Types. No significant correlation was found between salivary testosterone concentration (pg /ml) with the scores of the Nine Personality Types. No significant correlation was found between salivary testosterone concentration (pg/ml) and caries experience. Conclusions: The identification of Personality Types and their relations with dental caries can permit the assessment of the individual’s susceptibility and facilitate the improvement of the individual’s oral health. Keywords: Personality Types, caries experience, salivary testosterone.